FACTORS AFFECTING REGIONAL ORIGINAL INCOME IN WEST NUSA TENGGARA - Agus Tri Basuki; Titanika Kharisma (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research aims to analyze the influence of Gross Regional Domestic Product (GRDP), investment, government expenditure, and population on Regional Original Income (PAD) in West Nusa Tenggara (NTB) case study 2010-2022. The analytical tool used in this research is panel data regression with the Random Effect Model (REM). The research results show that GRDP has a negative and significant effect on Original Regional Income (PAD), investment has a positive and significant effect on Original Regional Income (PAD), government spending is not significant on Original Regional Income (PAD), and population has a positive and significant effect on Income. Regional Original (PAD). Regional governments must encourage investment to increase local original income. Apart from that, the government must also evaluate regional spending which cannot encourage an increase in PAD.